Transportasi Berkelanjutan dan Pengaruhnya terhadap Pengurangan Emisi di Kota Semarang - Safrinal Sofaniadi; Miftahul Huda; Fajar Hartawan (Jurnal Riptek, 2022)
One of the causes of congestion in the city of Semarang is the disproportion between the increase in the number of private vehicles and infrastructure development. Therefore, a comprehensive urban transportation development policy and program is needed to become a policy direction and program for improving connectivity, accessibility, mobility, safety, and environmental sustainability. The strategies in green and sustainable transportation are Spatial Planning Improvement, Public Transportation Service Improvement, Vehicle Technology Development, Environmentally Friendly Fuel Development, Traffic Engineering Management. From the results of the study. From this study Green transportation becomes an important part in the development of sustainable transportation. The Emission Reduction Strategy provides a BAU-compliant emission reduction from 22,408.9 kt CO2e to 16,006.4 kt CO2e